Grammatical Complexity in Research Articles: Iranian Local Journals and International Journals - Seyed Foad Ebrahimi; Samaneh Imandar (Issues in Language Teaching, 2021)
This study aimed to investigate the grammatical complexity based on Biber, Gray, Staples, and Egbert’s (2020) linguistic description in research articles published in Iranian local journals and international journals. The corpus of the study included 40 Applied Linguistics research articles, 20 published in Iranian local journals and 20 in international journals in 2019-2020. The research articles were selected through purposive sampling from two Iranian journals, namely Journal of Research in Applied Linguistics and Journal of Teaching Language Skills, and two international journals, including Journal of English for Specific Purposes and System Journal. The research articles were analyzed in terms of three dimensions of grammatical complexity, including the structural types, syntactic functions, and specific structural/syntactic features. Moreover, for intra-rater consistency, the researcher re-analyzed the corpus after one month to see whether the same results were found. According to the results, in terms of the first dimension, i.e., the structural types, the frequencies of structures indicating higher grammatical complexity (non-finite dependent clauses and dependent phrases) outnumbered the frequency of structures showing lower grammatical complexity (finite dependent clauses) in both local and international journals. Concerning the second dimension, i.e., syntactic function within the structural type, the frequencies of more complex syntactic functions were higher than those of simple functions in both sets of research articles. Concerning the third dimension, i.e., specific structural/syntactic features, both groups of writers preferred to use more complex specific structural/syntactic features than simple ones.